Financial Statement Design at Aura Taylor Business in Talaud Islands Regency - Essing, Anggriani Injilia; Sumual, Tinneke E. M; Lontoh, Miryam P (Klabat Accounting Review, 2024)
This research aims to apply the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM) and design financial statements for the Aura Taylor business using accounting software, specifically Microsoft Excel. The research utilizes a descriptive qualitative method, providing solutions regarding the use of Microsoft Excel software in preparing financial statements. The main instrument is the researchers themselves, with additional instruments including interview sheets and transaction documentation from the Aura Taylor business. This research shows that the entity has not yet applied the Financial Accounting Standards for Micro, Small, and Medium Enterprises. The financial recording process is still manual, consisting of cash receipts and cash disbursement records. The design of Aura Taylor's financial statements is created using functions, formulas, and menus in Microsoft Excel, forming a system comprising menus and submenus. The submenus include chart of accounts, general journal, ledger, worksheet, and financial statements which consist of the statement of financial position, income statement, and notes to the financial statements.